2017
DOI: 10.5539/ies.v10n6p150
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking What Is Entrepreneurship Education: A Macro Integrative Perspective

Abstract: Research on entrepreneurship education (EE) has encountered confusing ontological and methodological issues, such as definitional controversy, gaps between research and practice, and lack of theoretical foundations. These are factors holding back the further development of the research and practice in this field. This paper presents a whole picture of EE by exploring key factors involved in EE programs such as objective, audience, content and method, and assessment with a macro integrative perspective. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
6
0
4
Order By: Relevance
“…The benefit of increasing entrepreneurship to spur economic growth and employment is well understood within academic, business, and policy making communities around the world (Kuratko, 2005;Wu & Gu, 2017). Business dynamism in the United States, however, has been declining since the early 2000s (Decker, Haltiwanger, Jarmin, & Miranda, 2018;Fernald & Jones, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefit of increasing entrepreneurship to spur economic growth and employment is well understood within academic, business, and policy making communities around the world (Kuratko, 2005;Wu & Gu, 2017). Business dynamism in the United States, however, has been declining since the early 2000s (Decker, Haltiwanger, Jarmin, & Miranda, 2018;Fernald & Jones, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Disagreement continues about what activities and competencies are needed to build effective EE programming (Edelman, Manolova, & Brush, 2008;Williams Middleton & Donnellon, 2014;Mwasalwiba, 2010). In addition, a macro review noted ontological confusion and methodological issues in how EE is researched and taught (Wu & Gu, 2017). A 15-year review of the impact of EE up to 2015 revealed that minimal attention is paid to the impact of teaching approaches and methods (Kamovich & Foss, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ja -vorme (Arenguseire Keskus, 2018), nõuavad tööhõive tagamiseks ettevõtlikkust. Niisiis on ettevõtlus ja ettevõtlikkus (Hongyun Wu & Jibao Gu, 2017) saanud oluliseks peale ärisektori ka ühiskonnaelus laiemalt ning neis nähakse suurt potentsiaali nii majanduslike, sotsiaalsete kui ka kultuuriliste väärtuste ning innovatsiooni loomiseks ühiskonnas (Bacigalupo et al, 2016;Lackéus, 2015). Koos nende muutustega on muutunud ka arusaam sellest, mida mõistetakse ettevõtluse all.…”
unclassified
“…Ettevõtlusõpe tugineb usku musele, et ettevõtjaiks ei sünnita, vaid ettevõtluses tarvilik pädevus on aren datav ja ettevõtlusõppel on positiivne mõju ettevõtlus pädevuse arengule (Lans, Blok, & Wesselink, 2014;Lans, Ploum, & Baggen, 2018). Seega ei peaks ette võtlusõpe olema lõimitud mitte üksnes ärisektori, vaid ka teiste valdkondade õppekavadesse ning haarama paljusid sihtrühmi nii vanuse, tegevus valdkonna kui ka eri suguse ettevõtluskogemuse ja -profiili mõttes (Greene, Brush, Eisenman, Neck, & Perkins, 2016;Hongyun Wu & Jibao Gu, 2017;Lackéus, 2015;Venesaar et al, 2018). Ettevõtlusõppe tulemuslikkuse poolest on seniste uuringute andmed erinevad.…”
unclassified